Karakuduk Stone Workshop in Usturt Is Under New Research - Мadreymov Berik Djalgasbayevich (Genius Journals, 2023)
The Karakuduk flint workshop is located on the northern slopes of the Barsa-Kelmes depression in the Ustyurt plateau, 1.5-2 km north of the well of the same name. The workshop was opened by E.B. Bijanov in 1978. Surface finds were scattered over an area of 200x100 sq. m. The collection consists of more than 900 copies. artifacts. Some of them are heavily silicified slabs of siliceous limestone, and the other half are chips split from them. The tiles are small in size - in some cases their length exceeds 10 cm (mostly 5-10 cm), the average thickness is 1.5-2 cm. The length of most chips is 2-3 cm, and some specimens reach 5 cm. The workshop also revealed a series of bifacial worked tools. Different degrees of preservation of the surfaces collected at the Karakuduk workshop were noted. But these materials were not singled out for cultural-chronological complexes and according to the degree of preservation, and also were not studied technically and typologically properly. All the materials collected here by E. Bijanov were classified as Acheulean.
Keywords: Ustyurt; workshop; Karakuduk; biface